Implementation of Education 5.0 in Improving the Quality of Technology-Based Learning in Secondary Schools in Indonesia - Destari, Dina; Rifai, Muhammad (The Eastasouth Journal of Learning and Educations, 2025)
This study investigates the implementation of Education 5.0 in enhancing the quality of technology-based learning in secondary schools in Indonesia. Utilizing a quantitative research approach, data were collected from 150 respondents, including educators and students, through a structured questionnaire employing a Likert scale (1–5). Data analysis was conducted using SPSS version 25, incorporating descriptive statistics, correlation, and multiple regression analyses. The findings reveal a positive and significant relationship between Education 5.0 components—technology integration, personalized learning, teacher effectiveness, and student engagement—and the quality of learning. Among these, technology integration was identified as the most influential factor. The results underscore the transformative potential of Education 5.0 in creating interactive, learner-centered environments. However, challenges such as digital infrastructure disparities and teacher readiness must be addressed to maximize its benefits. This study provides valuable insights for policymakers, educators, and stakeholders in advancing educational innovation in Indonesia.